World on a Wire: Sound as Sensual Objects. - Johnson, Chuck (Leonardo Music Journal, 2013)
In the mid-20th century a new conceptual paradigm rose to prominence in the sciences that captured the imaginations of the burgeoning counterculture and its most forward-thinking artists. Against the backdrop of the Cold War, a branch of systems theory called cybernetics was presented as a way to understand complex systems. Cybernetic thought has continued to exert a hegemonic, if unintended, influence in the field of experimental and technologydriven arts. The author argues that the idealistic and technoutopian character of cybernetic thought, including the holistic view of emergence, does not serve us in grave political and ecological times and suggests new ways to understand emergence in sound art that are free of the ideological baggage of cybernetic thought.